Preparation method of sodium ferric sulfate composite positive electrode material of sodium ion battery

The Na2Fe2(SO4)3/C material was prepared by template reduction method, which solved the problem of unstable structure of sulfate positive electrode materials, achieved high crystallinity and high phase purity, and improved the energy density and cycle stability of sodium ion batteries.

CN119176583APending Publication Date: 2024-12-24SHENZHEN JANAENERGY TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411294850.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing sodium ion battery sulfate positive electrode materials are structurally unstable during the one-step synthesis process, resulting in high repulsion of Coulon, making it difficult to improve energy density and compaction density. The introduction of iron defects to reduce Coulon repulsion will affect the material performance.

Method used

Na2Fe2(SO4)3/C material was prepared by template reduction method, and Fe2(SO4)3 crystals were used as templates, and sodium ions were embedded with sodium reducing agents to form Na2Fe2(SO4)3/C composite with high crystallinity and high phase purity Materials, avoid iron deficiency vacancy and improve structural stability and electrochemical properties.

Benefits of technology

The high crystallinity, phase purity and compaction density of the material are achieved, the electrochemical performance and rate performance are improved, and the energy density and cycle stability of sodium ion batteries are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of a sodium ferric sulfate composite positive electrode material of a sodium ion battery, which comprises the following steps: S1, precursor solution mixing: mixing and dissolving an iron source, sulfuric acid and a non-metal-based oxidant, and reacting to generate a uniform precursor solution; the precursor solution is subjected to evaporative crystallization, Fe2 (SO4) 3 * xH2O crystals are generated, and x is larger than or equal to 0; s3, performing low-temperature calcination: performing low-temperature calcination on the Fe2 (SO4) 3. XH2O crystal to form a high-crystalline-state anhydrous Fe2 (SO4) 3 crystal; s4, preparing a Na2Fe2 (SO4) 3 / C mixture: uniformly mixing the Fe2 (SO4) 3 crystals, a sodium-containing reducing agent, an organic liquid carbon source and an inorganic solid carbon source, and filtering to obtain the Na2Fe2 (SO4) 3 / C mixture; and S5, performing high-temperature calcination: performing high-temperature calcination on the Na2Fe2 (SO4) 3 / C mixture in a protective atmosphere to form the Na2Fe2 (SO4) 3 / C composite positive electrode material. The preparation method of the sodium ferric sulfate composite positive electrode material of the sodium ion battery has the characteristics of high crystallinity and phase purity, high compaction density and good interface stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a method for preparing a sodium iron sulfate composite positive electrode material for a sodium ion battery. Background Art

[0002] The performance of cathode materials has a significant impact on the energy density and electrochemical performance of sodium-ion battery systems. Sodium-ion battery materials that are truly suitable for mass production need to meet the characteristics of low cost, high performance, and easy processing. However, the layered oxides, Prussian blue systems, and polyanion materials currently available on the market have different performances, and there are few materials with excellent comprehensive performance.

[0003] Sulfate materials are an important type of positive electrode materials for polyanion sodium ion batteries. They are rich in resources, simple in preparation process, high in voltage platform, and high in system energy density. Currently, the market positions them in the low-end power field. However, the edge-sharing arrangement of FeO6 octahedrons in the sulfate material structure causes Fe 3+ -Fe 3+ The Coulomb repulsion between them is large, and the structure is in a metastable state, making it difficult to synthesize by a one-step method.

[0004] In order to solve this problem, the Fe content in the structure is often reduced by introducing iron defects into the structure. 3+ -Fe 3+ The Coulomb repulsion between them stabilizes the structural framework, making it easy to prepare in batches. However, this method will reduce the content of transition metals that can be used for redox in the structure, reduce the specific capacity of the material, and is not conducive to improving its energy density. At the same time, the high iron defect content will also lead to a decrease in the densification of the material structure, seriously affecting the improvement of the material compaction density. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing a sodium iron sulfate composite positive electrode material for a sodium ion battery, which has the characteristics of high crystallinity and phase purity, high compaction density and good interface stability.

[0006] The present invention can be implemented by the following technical solutions: The invention discloses a method for preparing a Na2Fe2(SO4)3 / C positive electrode material for a sodium ion battery, comprising the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution; S2, evaporation crystallization: evaporating and crystallizing the above precursor solution to generate Fe2(SO4)3·xH2O crystals, wherein x≥0; S3, low temperature calcination: calcining the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals; Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are uniformly mixed, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, sodium ions are embedded in the crystals, and Na2Fe2(SO4)3 / C mixture is obtained by filtration; S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystallization growth of the material to form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability.

[0007] The key to the preparation of sulfate material stoichiometric compounds is to avoid Fe 3+ -Fe 3+ The Coulomb repulsion between them. The method for preparing the stoichiometric Na2Fe2(SO4)3 / C material of the present invention is characterized in that the structure does not contain iron vacancies, the iron site occupancy rate is as high as 100%, and it has a theoretical specific capacity of more than 120mAh / g. The process of the present invention adopts a template reduction method for synthesis, which uses Fe2(SO4)3 crystals as templates, and reduces Fe2(SO4)3 crystals in an organic solvent by a sodium-containing reducing agent to achieve the embedding of sodium ions in the structure, thereby achieving the controllable synthesis of metastable Na2Fe2(SO4)3 / C materials. The material prepared by the process of the present invention has high phase purity, good crystallinity, high compaction density, and excellent electrochemical properties.

[0008] In the present invention, the liquid carbon source can form a uniform and dense adhesion layer on the surface of the material. After calcination, the interface formed can greatly reduce the specific surface area of ​​the material, while blocking the side reaction of the electrolyte at the material interface and reducing the dissolution of elements on the surface of the material. The three-dimensional conductive network formed by the inorganic solid carbon source plays a role in connecting particles, which can realize the rapid conduction of electrons between particles. The synergistic combination of solid and liquid carbon sources significantly improves the stability of the material and its rate performance.

[0009] Furthermore, in step S1, the non-metallic-based oxidant is one or more of hydrogen peroxide, oxygen, and peracetic acid; its purpose is to oxidize the divalent iron in the solution, making it easier to combine with sulfate to form a three-dimensional framework compound, which is crystallized and precipitated during the subsequent evaporation of the solution. At the same time, after the non-metallic-based oxidant oxidizes the divalent iron, it will volatilize in the form of gas or in the subsequent evaporation process, and will not affect the purity of the Fe2(SO4)3·xH2O (x≥0) crystals.

[0010] Furthermore, in step S2, the temperature of evaporation and crystallization is 80-120°C. When the temperature is lower than 80°C, the water and excess oxidant in the solution cannot be completely removed, affecting subsequent experiments. When the temperature is higher than 120°C, the solution evaporation rate is too fast, Fe2(SO4)3·xH2O (x≥0) crystals precipitate too quickly, and the grain size is too small, affecting the compaction and electrochemical properties of the material.

[0011] Furthermore, in step S3, the low-temperature sintering temperature is 150-300°C. When the temperature is lower than 150°C, the moisture in the Fe2(SO4)3·xH2O (x≥0) crystals cannot be completely removed, affecting the subsequent sodium ion embedding. When the temperature is higher than 300°C, the Fe2(SO4)3 crystals will melt and solidify at high temperatures, which is not conducive to the operation of subsequent synthesis steps.

[0012] Furthermore, in step S5, the high temperature calcination temperature is 350-450°C, the purpose of which is to promote the reformation of elements in the Na2Fe2(SO4)3 structure, reduce the defect rate, and at the same time enhance the close fit of the Na2Fe2(SO4)3 / C composite interface to facilitate the transmission of electrons between the conductive agent and the crystal.

[0013] Further, in step S4, the sodium-containing reducing agent is one or more of sodium-naphthalene and sodium-biphenyl; Further, in step S4, the organic liquid carbon source is one or more of ether compounds, ketone compounds, and benzene compounds; the ether compound is one or more of tetrahydrofuran, dimethoxyethane, trihydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethyl ether, and 2-methyl-tetrahydrofuran; the ketone compound is one or more of 9-fluorenone b, benzophenone, acetone, and cyclohexanone; the benzene compound is one or more of 4-methylbiphenyl, toluene, xylene, phenol, etc.

[0014] Furthermore, in step S4, the inorganic solid carbon source is one or more of conductive carbon black and its derivatives, carbon nanotubes and their slurry, carbon fiber, graphene and its slurry, and flake graphite.

[0015] Further, in step S1, the iron source is one or a mixture of two or more of iron powder, ferrous oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous sulfate, and ferric sulfate.

[0016] Furthermore, in step S4, the filtering method is one or more of pressure filtration, vacuum filtration, and normal pressure filtration to achieve solid-liquid separation and remove excess organic solvent and sodium-containing reducing agent in the solution.

[0017] Furthermore, in step S5, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

[0018] The present invention provides a method for preparing a sodium iron sulfate composite positive electrode material for a sodium ion battery, which has the following beneficial effects: First, the crystallinity and phase purity are high. The present invention uses Fe2(SO4)3 crystals precipitated from the liquid phase as a template and utilizes the high efficiency of the sodium-containing reducing agent to achieve Na + Embedded in the template. Thanks to the orderly growth of Fe2(SO4)3 crystals during the liquid phase precipitation process, the template has high crystallinity and phase purity, and the content of defects and dislocations in the crystals is relatively small. Therefore, the reduced Na2Fe2(SO4)3 material still maintains the characteristics of high crystallinity and high phase purity.

[0019] Second, the compaction density is high. In the present invention, the Fe2(SO4)3 crystals are fully grown in the liquid phase precipitation process, and their compactness and primary particle size are large, and the compaction density is high. In the subsequent reduction process, Na+ is embedded in the Fe2(SO4)3 crystals to form Na2Fe2(SO4)3 materials, and the primary particle morphology and compaction structure characteristics are maintained, thereby having a higher compaction density; Third, the interface stability is good. In the present invention, the sodium-containing reducing agent reduces the Fe2(SO4)3 crystal in the process of reducing the active Na + It is embedded into the crystal lattice and forms a dense CEI film on the surface of the material. During the subsequent sintering process, its pyrolysis and shrinkage can form a dense conductive carbon layer, which effectively alleviates the dissolution of the material during the charge and discharge process, avoids the large-scale reduction and decomposition of the electrolyte on the surface of the material, and inhibits the repeated dissolution and regeneration of unstable CEI in subsequent cycles.

[0020] Excellent electrochemical performance: In the present invention, the Na2Fe2(SO4)3 material prepared using Fe2(SO4)3 crystals as a template has fewer defects, dislocations and other factors that affect the ion content and deintercalation rate. Therefore, it has a higher degree of crystallinity and phase purity, corresponding to a higher sodium storage content and unobstructed sodium ion diffusion channels in the structure, which enables the material to exhibit a higher reversible capacity and excellent rate performance. DETAILED DESCRIPTION

[0021] In order to enable those skilled in the art to better understand the technical solution of the present invention, the product of the present invention is further described in detail below in conjunction with embodiments.

[0022] The invention discloses a method for preparing a Na2Fe2(SO4)3 / C positive electrode material for a sodium ion battery, comprising the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution; S2, evaporation crystallization: evaporating and crystallizing the above precursor solution to generate Fe2(SO4)3·xH2O crystals, wherein x≥0; S3, low temperature calcination: calcining the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals; Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are uniformly mixed, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, and Na2Fe2(SO4)3 / C mixture is obtained by filtration; S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystallization growth of the material to form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability.

[0023] Furthermore, in step S1, the non-metal-based oxidant is one or more of hydrogen peroxide, oxygen, and peracetic acid.

[0024] Further, in step S2, the temperature of evaporation crystallization is 80-120°C.

[0025] Furthermore, in step S3, the low temperature sintering temperature is 150-300°C.

[0026] Furthermore, in step S5, the high temperature calcination temperature is 350-450°C.

[0027] Further, in step S4, the sodium-containing reducing agent is one or more of sodium-naphthalene and sodium-biphenyl; Further, in step S4, the organic liquid carbon source is one or more of ether compounds, ketone compounds, and benzene compounds; the ether compound is one or more of tetrahydrofuran, dimethoxyethane, trihydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethyl ether, and 2-methyl-tetrahydrofuran; the ketone compound is one or more of 9-fluorenone b, benzophenone, acetone, and cyclohexanone; the benzene compound is one or more of 4-methylbiphenyl, toluene, xylene, phenol, etc.

[0028] Furthermore, in step S4, the inorganic solid carbon source is one or more of conductive carbon black and its derivatives, carbon nanotubes and their slurry, carbon fiber, graphene and its slurry, and flake graphite.

[0029] Further, in step S1, the iron source is one or a mixture of two or more of iron powder, ferrous oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous sulfate, and ferric sulfate.

[0030] Furthermore, in step S4, the filtering method is one or more of pressure filtration, vacuum filtration, and normal pressure filtration.

[0031] Furthermore, in step S5, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

[0032] Example 1 This embodiment relates to a sodium ion battery Na2Fe2(SO4)3 / C positive electrode material, and its preparation method comprises the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant, and reacting to generate a uniform precursor solution. Specifically, the non-metallic oxidant is hydrogen peroxide or peracetic acid; the iron source is ferrous oxide, ferrous oxide, ferrous sulfate, or ferric sulfate.

[0033] S2, evaporation crystallization: evaporate and crystallize the above precursor solution to generate Fe2(SO4)3·xH2O crystals, where x≥0. Specifically, the evaporation crystallization temperature is 80°C.

[0034] S3, low temperature calcination: calcine the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals. Specifically, the low temperature sintering temperature is 300°C.

[0035] Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are mixed evenly, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, and Na2Fe2(SO4)3 / C mixture is obtained by filtration. Specifically, the sodium-containing reducing agent is sodium-naphthalene and sodium-biphenyl; the organic liquid carbon source is a benzene compound, and the benzene compound is 4-methylbiphenyl, toluene, xylene, and phenol; the inorganic solid carbon source is conductive carbon black and its derivatives, graphene and its slurry, and flake graphite; the filtration method is normal pressure filtration.

[0036] S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystal growth of the material and form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability. Specifically, the high-temperature calcination temperature is 400°C; the protective atmosphere is nitrogen or argon.

[0037] Example 2 This embodiment relates to a sodium ion battery Na2Fe2(SO4)3 / C positive electrode material, and its preparation method comprises the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution. Specifically, the non-metallic oxidant is hydrogen peroxide; the iron source is iron powder, ferrous oxide, or ferric oxide.

[0038] S2, evaporation crystallization: evaporate and crystallize the above precursor solution to generate Fe2(SO4)3·xH2O crystals, where x≥0. Specifically, the evaporation crystallization temperature is 20°C.

[0039] S3, low temperature calcination: calcining the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals. Specifically, the low temperature sintering temperature is 230°C.

[0040] Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are uniformly mixed, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, and Na2Fe2(SO4)3 / C mixture is obtained by filtration. Specifically, the sodium-containing reducing agent is sodium-naphthalene; the organic liquid carbon source is an ether compound, and the ether compound is tetrahydrofuran, dimethoxyethane, trihydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether; the inorganic solid carbon source is conductive carbon black and its derivatives; the filtering method is filter pressing.

[0041] S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystal growth of the material and form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability. Specifically, the high-temperature calcination temperature is 350°C; the protective atmosphere is nitrogen or argon.

[0042] Example 3 This embodiment relates to a sodium ion battery Na2Fe2(SO4)3 / C positive electrode material, and its preparation method comprises the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant, and reacting to generate a uniform precursor solution. Specifically, the non-metallic oxidant is peracetic acid; the iron source is ferric hydroxyhydroxide, ferrous sulfate, or ferric sulfate.

[0043] S2, evaporation crystallization: evaporate and crystallize the above precursor solution to generate Fe2(SO4)3·xH2O crystals, where x≥0. Specifically, the evaporation crystallization temperature is 100°C.

[0044] S3, low temperature calcination: calcining the Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals. Specifically, the low temperature sintering temperature is 150°C.

[0045] Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are mixed evenly, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, and Na2Fe2(SO4)3 / C mixture is obtained by filtration. Specifically, the sodium-containing reducing agent is sodium-biphenyl; the organic liquid carbon source is a ketone compound, and the ketone compound is 9-fluorenone b, benzophenone, acetone, and cyclohexanone; the inorganic solid carbon source is carbon fiber, graphene and its slurry, and flake graphite; the filtering method is vacuum filtration.

[0046] S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystal growth of the material and form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability. Specifically, the high-temperature calcination temperature is 450°C; the protective atmosphere is nitrogen-hydrogen or argon-hydrogen.

[0047] Example 4 This embodiment relates to a sodium ion battery Na2Fe2(SO4)3 / C positive electrode material, and its preparation method comprises the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution. Specifically, the non-metallic oxidant is hydrogen peroxide and oxygen; the iron source is ferric hydroxyhydroxide, ferrous sulfate, and ferric sulfate.

[0048] S2, evaporation crystallization: evaporate and crystallize the above precursor solution to generate Fe2(SO4)3·xH2O crystals, where x≥0. Specifically, the evaporation crystallization temperature is 90°C.

[0049] S3, low temperature calcination: calcining the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals. Specifically, the low temperature sintering temperature is 220°C.

[0050] Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are mixed evenly, trivalent iron in Fe2(SO4)3 crystals is reduced by sodium-containing reducing agent, and Na2Fe2(SO4)3 / C mixture is obtained by filtration. Specifically, the sodium-containing reducing agent is sodium-naphthalene and sodium-biphenyl; the organic liquid carbon source is ketone compounds and benzene compounds, the ketone compounds are benzophenone, acetone, cyclohexanone, and the benzene compound is 4-methylbiphenyl; the inorganic solid carbon source is graphene and its slurry, and flake graphite; the filtration method is filter pressing.

[0051] S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystal growth of the material and form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability. Specifically, the high-temperature calcination temperature is 380°C; the protective atmosphere is nitrogen or argon.

[0052] Example 5 This embodiment relates to a sodium ion battery Na2Fe2(SO4)3 / C positive electrode material, and its preparation method comprises the following steps: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution. Specifically, the non-metallic oxidant is peracetic acid; the iron source is ferric hydroxyhydroxide, ferrous sulfate, or ferric sulfate.

[0053] S2, evaporation crystallization: evaporate and crystallize the above precursor solution to generate Fe2(SO4)3·xH2O crystals, where x≥0. Specifically, the evaporation crystallization temperature is 110°C.

[0054] S3, low temperature calcination: calcine the Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals. Specifically, the low temperature sintering temperature is 200°C.

[0055] Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are mixed evenly, and the trivalent iron in the Fe2(SO4)3 crystals is reduced by the sodium-containing reducing agent, and the Na2Fe2(SO4)3 / C mixture is obtained by filtration. Specifically, the sodium-containing reducing agent is sodium-naphthalene and sodium-biphenyl; the organic liquid carbon source is ether compounds, ketone compounds and benzene compounds, the ether compounds are tetraethylene glycol dimethyl ether, dimethyl ether and 2-methyl-tetrahydrofuran, the ketone compounds are benzophenone, acetone and cyclohexanone, and the benzene compounds are toluene, xylene and phenol; the inorganic solid carbon source is conductive carbon black and its derivatives; the filtering method is vacuum filtration.

[0056] S5. High-temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to promote further crystal growth of the material and form a Na2Fe2(SO4)3 / C composite positive electrode material with high structural stability. Specifically, the high-temperature calcination temperature is 380°C; the protective atmosphere is nitrogen or argon.

[0057] Application Example 1 Synthesis and electrochemical performance of Na2Fe2(SO4)3 / C material by template reduction method This embodiment relates to Na2Fe2(SO4)3 / C material, and its preparation process is prepared by template reduction method, which specifically includes the following steps: Step 1: Dissolve atomized elemental iron powder and sulfuric acid in water at a molar ratio of 2:3, and add hydrogen peroxide as an oxidizing agent at a molar amount of half that of the elemental iron powder to form a uniform solution; Step 2: Slowly evaporate the above solution at 100°C to remove water and excess hydrogen peroxide in the solution, and initially form Fe2(SO4)3·xH2O (x≥0) hydrated phase crystals; Step 3: calcining the hydrated phase crystals at 200°C to further remove the crystal water in the crystals to form highly crystalline anhydrous Fe2(SO4)3 crystals; Step 4: Add Fe2(SO4)3 crystals and sodium-naphthalene in a molar ratio of 1:2 to 9-fluorenone b organic solvent, and add carbon nanotubes with a total solid content of 1.5% as a conductive agent, use a sodium-containing reducing agent to reduce the trivalent iron in the Fe2(SO4)3 crystals, and embed sodium ions into the crystals, and filter to obtain a Na2Fe2(SO4)3 / C complex; Step 5: Under a nitrogen atmosphere, the Na2Fe2(SO4)3 / C complex is calcined at 400°C to promote further crystallization growth of the material to form a Na2Fe2(SO4)3 / C composite material with high structural stability.

[0058] The performance test results of the material are shown in Table 1. The results in Table 1 show that the specific surface area of ​​the material is 4.3m 2 / g, compared with the liquid phase method in Comparative Example 1 and the solid phase method in Comparative Example 2, its specific surface area is significantly reduced, indicating that the Na2Fe2(SO4)3 / C composite material prepared using Fe2(SO4)3 crystals as templates has a lower porosity and a higher density, which corresponds to the fact that the template reduction method can form large-grained single crystals. The decrease in specific surface area has a significant improvement in the back-end manufacturing of the material and the performance and maintenance of the electrochemical performance. In addition, using XRD refinement, it can be identified that the phase purity of the Na2Fe2(SO4)3 / C composite material is as high as 99.3%, indicating that there are fewer components that affect the crystallinity of the material, such as internal defects and dislocations in the structure. It also proves that the materials prepared based on the template reduction method have excellent process feasibility, while the phase purity of the materials in Comparative Examples 1 and 2 is lower, which is related to the larger Coulomb repulsion in the material structure in the one-step synthesis method and the lower degree of mixing uniformity between the raw materials.

[0059] The Na2Fe2(SO4)3 / C composite material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After grinding, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.

[0060] The above button cell was subjected to constant current charge and discharge test, and the current density was 0.1C (1C=120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is 115.3mAh / g, and the capacity utilization is greatly improved compared with Comparative Examples 1 and 2, which is related to the high phase purity of the material and the high content of active transition metal ions in the structure. The higher the phase purity of the material, the higher the transition metal content per unit mass, the more sodium ions can be used for redox, the fewer factors affecting ion diffusion in the crystal, and the higher the capacity utilization rate. In addition, the results in Table 1 show that the capacity retention rate of the material at 10C is 95.4% of 0.1C, showing excellent rate performance, which is better than the performance of the material performance in Comparative Examples 1 and 2, indicating that the ion migration kinetics in the material prepared by the template reduction method are relatively fast, and the transition velocity is high at high currents, and the energy barrier is low, which is associated with the material having a small defect rate. Finally, the electrode has a capacity retention rate of up to 97.6% after 500 cycles at a rate of 1C, showing excellent structural stability and cycle stability compared to Comparative Examples 1 and 2. This indicates that the material prepared by the template reduction method has a smaller specific surface area, a high crystal density, and a relatively uniform volume expansion anisotropy during the embedding and de-embedding process. At the same time, the lower specific surface area reduces the degree of side reactions between the electrode and the electrolyte, effectively inhibiting the dissolution of the material interface, thereby improving its cycle stability.

[0061] Comparative Example 1 Synthesis of Na2Fe2(SO4)3 / C material by liquid phase method and its electrochemical performance This embodiment relates to Na2Fe2(SO4)3 / C material, and its preparation process is prepared by liquid phase method, which specifically includes the following steps: Step 1: Dissolve ferrous sulfate heptahydrate and anhydrous sodium sulfate in water at a molar ratio of 2:1, add a small amount of ascorbic acid (weight ratio is 1% of the molar amount of iron) to avoid oxidation of divalent iron ions, and finally add a small amount of carbon nanotube aqueous slurry as a conductive agent (weight ratio is 2% of the total solid content in the solution), and stir thoroughly to generate a uniform black slurry; Step 2: spray-dry the above slurry and control the outlet air temperature to ≥90°C to obtain a uniform precursor powder; Step 3: calcine the precursor powder at 400°C under nitrogen protection to promote material melting and crystal growth, and naturally cool down to obtain the Na2Fe2(SO4)3 / C composite material.

[0062] The test results are shown in Table 1. The results in Table 1 show that the specific surface area of ​​the material is 10.6m 2 / g, which is significantly increased compared with Application Example 1, indicating that the primary particles prepared by the liquid phase spray method are finer, and there are a large number of pores between the particles, resulting in an increase in specific surface area, which will affect the subsequent homogenization of the material and the stable performance of the electrochemical performance to a certain extent. In addition, we used XRD refinement to find that the phase purity of the material is only 85.9%, and there are a large number of impurity phases. This is related to the strong repulsive force between Fe-Fe in the crystal structure of the material during the one-step synthesis process, which leads to the instability of the metastable structure of the material during the sintering process and the inability to form a high-purity phase.

[0063] The Na2Fe2(SO4)3 / C composite material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After grinding, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and the diaphragm was a PP / PE / PP three-layer diaphragm, and assembled into a CR2016 button cell in a glove box.

[0064] The button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is only 89.2mAh / g, and the capacity is far lower than the performance of the material in Application Example 1. This is related to the lower phase purity of the material. The lower the phase purity of the material, the lower the effective active material component per unit mass, resulting in a decrease in the number of redox charges, which in turn affects the performance of the material capacity. In addition, the rate performance test results show that at a rate of 10C, the capacity retention rate of the material synthesized by the solid phase method relative to 0.1C is only 78.3%, which is far lower than the performance of the pure phase material in Application Example 1, indicating that the presence of the impurity phase or the decrease in the crystallinity of the material will hinder the migration of sodium ions at high current density, thereby resulting in a significant decrease in its rate performance. Finally, the results in Table 1 show that within the voltage range of 2.0-4.3V, the capacity retention rate of the electrode after 500 cycles at a rate of 1C is only 82.4%, which is much lower than the material performance in Application Example 1. The lower cycle stability of the material comes from its larger specific surface area, which leads to the aggravation of the side reaction with the electrolyte at high voltage, affecting the interface stability of the material. On the other hand, the lower phase purity of the material leads to uneven local volume expansion during the sodium ion extraction and insertion process, which easily induces lattice rupture and other problems, ultimately leading to a decrease in the cycle stability of the material.

[0065] Comparative Example 2 Synthesis of Na2Fe2(SO4)3 / C material by solid phase method and its electrochemical performance This embodiment relates to Na2Fe2(SO4)3 / C material, and its preparation process is prepared by solid phase method, which specifically includes the following steps: Step 1: Add anhydrous ferrous sulfate and anhydrous sodium sulfate into a ball mill at a molar ratio of 2:1, and add some carbon nanotubes as a conductive agent (weight ratio is 2% of the total solid content), the ball-to-material ratio is controlled at 20:1, and the grinding time is greater than 10 hours; Step 2: Under nitrogen protection, the precursor powder is calcined at 400°C to promote material melting and crystal growth, and the Na2Fe2(SO4)3 / C material is obtained by natural cooling.

[0066] The test results are shown in Table 1. The results in Table 1 show that the specific surface area of ​​the material is 13.5m 2 / g, which is larger than that of the template reduction method in Application Example 1, indicating that the particle size of the material powder produced by solid phase ball milling is small, and at the same time, the carbon nanotube conductive agent is repeatedly broken during grinding, exposing many new interfaces, resulting in an excessively large specific surface area of ​​the final material. The large specific surface area has a significant impact on the subsequent processing and performance of the material. In addition, through the refinement of the XRD curve, it was found that the phase purity of the material was only 74.2%, the crystallinity was low, the crystal form integrity was not high, and the impurity content was high. On the one hand, this was related to the uneven distribution of ions during the solid phase grinding process, and on the other hand, it was related to the large Coulomb repulsion between Fe-Fe in the crystal structure during the one-step synthesis during the material sintering process. The combination of these two factors ultimately led to a significant decrease in the phase purity of the material.

[0067] Na2Fe2(SO4)3 / C material, AB, and PVDF were mixed and slurried in a mass ratio of 9.2:0.4:0.4. After grinding, the black slurry was coated on aluminum foil using a 150um four-sided preparation device, and then the film was dried in a vacuum drying oven at 100°C for 2 hours. The electrode film was punched into a disc with a radius of 0.6mm using a punching machine, with metallic sodium as the counter electrode, 1mol / LNaClO4EC+DEC (1:1vol%)+5%FEC as the electrolyte, and a PP / PE / PP three-layer diaphragm as the separator, and assembled into a CR2016 button cell in a glove box.

[0068] The above button cell was subjected to constant current charge and discharge test with a current density of 0.1C (1C=120mAh / g). The results in Table 1 show that within the voltage range of 2.0-4.5V, the reversible specific capacity of the electrode is 64.7mAh / g, and the capacity is far lower than that of Application Example 1, indicating that the material prepared by the solid phase method has a low phase purity, low crystallinity, and a small proportion of active substances, resulting in a significant decrease in the actual capacity of the material. In addition, the rate performance test results show that at a rate of 10C, the capacity retention rate of the material is only 54.2% compared to 0.1C, and the rate performance is poor, which is related to the low ionic conductivity in the material, indicating that the presence of more impurity phases will increase the energy barrier in the ion migration process, seriously hindering the rapid migration of ions, resulting in a significant decrease in its rapid charge and discharge capability. Finally, the results in Table 1 show that within the voltage range of 2.0-4.3V, the capacity retention rate of the electrode at 1C rate after 500 cycles is only 76.5%. Compared with Application Example 1, the stability decreases significantly, which may be related to the presence of impurities in the material, resulting in uneven volume changes caused by structural expansion / contraction during the sodium insertion and extraction process, inducing crystal cracking. In addition, the large specific surface area of ​​the material will also accelerate the side reaction between the interface of the material and the electrolyte, resulting in a continuous deterioration of the material's cyclic stability.

[0069] Table 1 Performance test results The above embodiments are only specific embodiments of the present invention, and their descriptions are relatively specific and detailed, but they cannot be understood as limiting the scope of the present invention. It should be pointed out that for ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and these obvious replacement forms all belong to the protection scope of the present invention.

Claims

1. A method for preparing a Na2Fe2(SO4)3 / C positive electrode material for a sodium ion battery, characterized in that The following steps are involved: S1. Precursor solution mixing: mixing and dissolving an iron source, sulfuric acid, and a non-metallic oxidant to react and generate a uniform precursor solution; S2, evaporation crystallization: evaporating and crystallizing the above precursor solution to generate Fe2(SO4)3·xH2O crystals, wherein x≥0; S3, low temperature calcination: calcining the above Fe2(SO4)3·xH2O crystals at low temperature to form highly crystalline anhydrous Fe2(SO4)3 crystals; Preparation of S4, Na2Fe2(SO4)3 / C mixture: Fe2(SO4)3 crystals, sodium-containing reducing agent, organic liquid carbon source and inorganic solid carbon source are uniformly mixed, and filtered to obtain Na2Fe2(SO4)3 / C mixture; S5. High temperature calcination: Under a protective atmosphere, the Na2Fe2(SO4)3 / C mixture is calcined at a high temperature to form a Na2Fe2(SO4)3 / C composite positive electrode material.

2. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S1, the non-metal-based oxidant is one or more of hydrogen peroxide, oxygen and peracetic acid.

3. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S2, the temperature of evaporation crystallization is 80-120°C.

4. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S3, the low temperature sintering temperature is 150-300°C.

5. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S5, the high temperature calcination temperature is 350-450°C.

6. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S4, the sodium-containing reducing agent is one or more of sodium-naphthalene and sodium-biphenyl.

7. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 6, characterized in that: In step S4, the organic liquid carbon source is one or more of ether compounds, ketone compounds, and benzene compounds; the ether compound is one or more of tetrahydrofuran, dimethoxyethane, trihydrofuran, ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethyl ether, and 2-methyl-tetrahydrofuran; the ketone compound is one or more of 9-fluorenone b, benzophenone, acetone, and cyclohexanone; the benzene compound is one or more of 4-methylbiphenyl, toluene, xylene, phenol, etc.

8. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S4, the inorganic solid carbon source is one or more of conductive carbon black and its derivatives, carbon nanotubes and their slurry, carbon fibers, graphene and its slurry, and flake graphite.

9. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S1, the iron source is one or a mixture of two or more of iron powder, ferrous oxide, ferrous oxide, ferric oxide, ferric hydroxide, ferrous sulfate, and ferric sulfate.

10. The method for preparing the sodium iron sulfate composite positive electrode material for sodium ion batteries according to claim 1, characterized in that: In step S4, the filtering method is one or more of pressure filtration, vacuum filtration, and normal pressure filtration; In step S5, the protective atmosphere is one or more of nitrogen, argon, nitrogen-hydrogen, and argon-hydrogen.

Citation Information

Cited By

  • Composite sodium source sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN120237207A

  • Sodium ferric sulfate positive electrode material as well as preparation method and application thereof

    CN121516917A